Corneal Biomechanics Determination in Healthy Myopic Subjects - Kunliang Qiu; Xuehui Lu; Riping Zhang; Geng Wang; Mingzhi Zhang (Journal of Ophthalmology)
Purpose. To determine the corneal biomechanical properties by using the Ocular Response Analyzer™ and to investigate potential factors associated with the corneal biomechanics in healthy myopic subjects. Methods. 135 eyes from 135 healthy myopic subjects were included in this cross-sectional observational study. Cornea hysteresis (CH), corneal resistance factor (CRF), cornea-compensated intraocular pressure (IOPcc), and Goldmann-correlated intraocular pressure (IOPg) were determined with the Reichert Ocular Response Analyzer (ORA). Univariate and multivariate regression analyses were performed to investigate factors associated with corneal biomechanics. Results. The mean CH and CRF were 9.82±1.34 mmHg and 9.64±1.57 mmHg, respectively. In univariate regression analysis, CH was significantly correlated with axial length, refraction, central corneal thickness (CCT), and IOPg (r=-0.27, 0.23, 0.45, and 0.21, resp.; all with p≤0.015), but not with corneal curvature or age; CRF was significantly correlated with CCT and IOPg (r=0.52 and 0.70, resp.; all with p<0.001), but not with axial length/refraction, corneal curvature, or age. In multivariate regression analysis, axial length, IOPcc, and CCT were found to be independently associated with CH, while CCT and IOPg were associated with CRF. Conclusions. Both CH and CRF were positively correlated with CCT. Lower CH but not CRF was associated with increasing degree of myopia. Evaluation of corneal biomechanical properties should take CCT and myopic status into consideration.